2023
DOI: 10.1021/acsomega.3c06799
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Insights into the Molecular Interactions between Human Transferrin and Apigenin: Implications of Natural Compounds in Targeting Neuroinflammation

Moyad Shahwan,
Saleha Anwar,
Dharmendra Kumar Yadav
et al.

Abstract: Neuroinflammation plays a vital role in Alzheimer’s disease (AD) pathogenesis and other neurodegenerative disorders (NDs). Presently, only symptomatic treatments are available and no disease-modifying drugs are available for AD and other NDs. Thus, targeting AD-associated neuroinflammation with anti-inflammatory compounds and antioxidants has recently been given much focus. Now, flavonoids are being increasingly investigated as therapeutic agents to treat inflammation; apigenin has a neuroprotective effect. Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In a GFAP-IL6 (glial fibrillary acidic protein-interleukin 6) transgenic mouse model, a model exhibiting neuronal loss and atrophy, chronic activation of microglia and astrocytes, increased expression of inflammatory mediators [99], and BBB disruption and age-related motor and cognitive impairment [99][100][101], apigenin decreased the number of Iba-1+ microglia in the hippocampus of GFAP-IL6 mice and altered microglial morphology, but no reversal of spatial memory impairment was observed [102]. In computational and experimental studies by Shahwan et al targeting Alzheimer's disease, apigenin was shown to occupy the iron-binding pocket of human transferrin [103]. The authors were interested in the transferrin/apigenin complex because iron dyshomeostasis plays an important role in maintaining the neuroinflammatory phenotype, demonstrating the importance of maintaining iron balance [103].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In a GFAP-IL6 (glial fibrillary acidic protein-interleukin 6) transgenic mouse model, a model exhibiting neuronal loss and atrophy, chronic activation of microglia and astrocytes, increased expression of inflammatory mediators [99], and BBB disruption and age-related motor and cognitive impairment [99][100][101], apigenin decreased the number of Iba-1+ microglia in the hippocampus of GFAP-IL6 mice and altered microglial morphology, but no reversal of spatial memory impairment was observed [102]. In computational and experimental studies by Shahwan et al targeting Alzheimer's disease, apigenin was shown to occupy the iron-binding pocket of human transferrin [103]. The authors were interested in the transferrin/apigenin complex because iron dyshomeostasis plays an important role in maintaining the neuroinflammatory phenotype, demonstrating the importance of maintaining iron balance [103].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…In computational and experimental studies by Shahwan et al targeting Alzheimer's disease, apigenin was shown to occupy the iron-binding pocket of human transferrin [103]. The authors were interested in the transferrin/apigenin complex because iron dyshomeostasis plays an important role in maintaining the neuroinflammatory phenotype, demonstrating the importance of maintaining iron balance [103]. The binding between apigenin and transferrin is relatively stable, so this could open new therapeutic opportunities using apigenin to control iron homeostasis and, hence, neuroinflammation.…”
Section: Alzheimer's Diseasementioning
confidence: 99%